PENERAPAN MEDIA GAMBAR UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS I SD NEGERI 011 AIR EMAS - Kartina, Kartina (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
In the process of learning Social Sciences is very necessary for the right and optimal learning for students by teachers both intellectually and emotionally, so that ideal conditions are created in the learning process. But the learning process carried out by the teacher is very far from the ideal word, this is due to the weak learning process developed by the teacher. The purpose of this study was to improve the learning outcomes of students' Social Sciences by applying media images. This study uses classroom action research which consists of 4 stages, such as; planning, observation, implementation and reflection. As for the results of the study, judging from the initial completeness, as many as 13 students or 43.3% of students who completed the Minimum Completion Criteria, while the students who were not completed were 17 students or 56.6% with a class average of 63.4. In the first cycle, as many as 21 students or 70% had completed reaching the Minimum Completion Criteria, while students who had not yet completed reached the Minimum Completion Criteria as many as 9 students or 30% with a class average value of 73.2. For the second cycle, as many as 26 students or 86.6% had completed reaching the Minimum Completion Criteria and only 4 students or 13.3% had not yet completed reaching the Minimum Completion Criteria.